North–South asymmetry, unilateral environmental policy and carbon tariffs. (13th July 2022) - Hong, Liming; Huang, Wei; Anwar, Sajid; Lv, Xiaofeng
Abstract: This paper focuses on the potential impact of a carbon tariff on carbon emissions, North–South trade and welfare. We use a North–South trade model, where North implements a unilateral environmental policy on domestic carbon‐intensive industries followed by a carbon tariff on imports from South. Unlike the existing studies, we allow asymmetry in clean production technologies and marginal environmental damage. We show that a carbon tariff can reduce the global carbon emission via the use of a more advanced clean production technology in North, which increases the firm profit and welfare. However, improvement in welfare of North is associated with a decrease in global trade flows and welfare of South. We find that, in the presence of asymmetry in clean production technologies between North and South, a carbon tariff introduced by the North can eliminate carbon leakage, but the exports of South decrease below the pre‐unilateral environmental policy level and hence North can potentially use a carbon tariff for trade protectionism in the name of reducing carbon leakage in South.